An Analysis of Class-as-Race and Gender Ideology in the US Young Adult Sports Novel Racing Savannah (2013) - Riestra-Camacho, Rocío (International Journal of English Studies, 2020)
Equine fiction is an established genre in the English juvenile literary canon. Current works in the field appeal to adolescent readers thanks to their interface between classic motifs of vintage and contemporary forms of equine narratives. Performing a close reading of selected passages in Miranda Kenneally’s Racing Savannah (2013), this paper acknowledges how this novel is a revitalization and a challenge to this pattern. Savannah, who is more gifted than her companions, is subordinate to the decisions of the junior of the household where she works. Jack Goodwin, the protagonist’s romantic lead, educated in a neocolonialist background of male jockeying, becomes Savannah’s marker of difference according to her sex and lower socioeconomic status, which lay at the root of her later racialization despite her being a white character. My analysis attempts to expose how these difficulties encountered by the protagonist to become a professional jockey articulate past and present constraints of the horse-racing ladder.